The Competence of Arabic Language Teachers in The Digital Era: A Study Based on The Technological Pedagogical Content Knowledge (TPACK) Framework - Shofwan Sholahudin; Yayan Nurbayan; Mad Ali (Dinasti Publisher, 2025)
The digital era demands Arabic language teachers to possess integrated competencies, encompassing Content Knowledge, Pedagogical Knowledge, and Technological Knowledge within the Technological Pedagogical Content Knowledge (TPACK) framework. This study aims to analyze the competencies of Arabic language teachers in Indonesia in addressing the challenges of the Society 5.0 era using a Systematic Literature Review (SLR) approach. The analysis was conducted on 17 relevant studies. The findings reveal that most teachers have adequate content and pedagogical knowledge; however, the integration of technology in teaching remains limited. Teachers tend to utilize technology at a basic level, such as for communication and information sources, without fully leveraging its potential to support innovative and interactive teaching. This study recommends structured TPACK training, improved access to technology, and the development of teacher communities to share best practices. These findings provide strategic guidance for enhancing the quality of Arabic language teaching to meet the needs of the digital era.